Specialised early intervention teams for first episode psychosis - Puntis, S; Minichino, A; De Crescenzo, F; Cipriani, A; Lennox, B (Cochrane Collaboration, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To compare early intervention in psychosis (EIP) specialised teams to usual community mental health care for the treatment of people with first episode psychosis (FEP).